ANALISIS PENDAPATAN USAHATANI TANAMAN JAGUNG DI DESA TONGKE KECAMATAN BALANTAK SELATAN - Salatun, Sella Nuraisya; Zaenuddin, Ruslan A; Puspapratiwi, Dian (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2023)
Extension workers have a strategic role in guiding farmers to increase the productivity of corn crop farming. This study aims to determine the role of agricultural extension workers in improving farming in South Balantak District. This research was carried out from November 2022 to January 2023 in Tongke Village, South Balantak District. The population in this study is a farmer group in Tongke Village. This study used methods with likert and income analysis. The income obtained by farmers in Tongke Village, South Balantak District, obtained from the reduction between Total revenue (TR) of Rp. 96,000,000.00 and Total cost (TC) of Rp. 701,500.00, then income (π) = TR – TC is Rp. 95,298,500. This means that corn farming can still be cultivated or developed by farmers in Tongke Village, South Balantak District, Banggai Regency, because the amount of income obtained is still quite high.